The element of service quality which most contributes to customer satisfaction in using Unipeq Sdn. Bhd. services / Norlisha Bujang - Bujang, Norlisha (Faculty of Business and Management, 2010)
UNIPEQ Sdn Bhd is a Food Quality Research Unit of Universiti Kebangsaan Malaysia was established in May 1994 which has been actively involved in playing a more direct role towards the development of the local food industry. UNIPEQ provide three kin of service which are Laboratory service, Training service and Consultancy service. This study main focusing on the relationship between the elements of service quality (SERVQUAL) which has five main dimensions (tangibles, reliability, responsiveness, assurance, and empathy) and customer satisfaction. In addition, this study also determines the element which most contributes to customer satisfaction. By giving the overview of the topic discussed, it will help the company to know whether the customer are satisfied with the services provide by them and company can do some improvement if dissatisfaction occur during the service deliver. This study requires 50 respondents of UNIPEQ’s regular customer which cover all state in Malaysia which mean this study is using the probability sampling and applied the stratified technique. The questionnaires are design from open ended and close ended questions where the question divided into three section included Likert Scale style. Questionnaires forms are distributed to them and then all the feedbacks analyze by using data analysis software called SPSS version 14. Through this software, reliability test, frequency distribution test, Pearson correlation coefficient analysis and descriptive test are been used. Based on finding from analysis data, researcher found there is significant relationship between all the elements of service quality and customer satisfaction at 0.01 significant level. Furthermore, responsiveness element is the element which most contributes to customer satisfaction at 3.9640, the highest mean values. Researcher also gives some recommendation and suggestion to UNIPEQ so that they can improve their service quality in order to increase customer satisfaction. Immediate and corrective action towards the complaints is needed since it will enable organization improve the defective customer services because customers are came from various level of satisfaction. Plus, increase the warmth because customers face very tough routine every day and they need comfortable and peace condition if dealing with service provider as well as the customers always right. And lastly, customers as human being, appreciation is like very honourable. Customers always seek suppliers and service provided which appreciate them well and by organizing any activities to celebrate their loyalty, they are also willing to promote the organization to other people.